Sperm selected by both birefringence and motile sperm organelle morphology examination have reduced deoxyribonucleic acid fragmentation - Garolla, Andrea; Cosci, Ilaria; Menegazzo, Massimo; De Palo, Raffaella; Ambrosini, Guido; Sartini, Barabara; Pizzol, Damiano; Foresta, Carlo (Fertility and sterility, 2014)
To evaluate DNA fragmentation in single sperm selected by both birefringence and motile sperm organelle morphology examination (MSOME) with a single instrument. Prospective study. University setting. Semen samples from 33 normozoospermic subjects. Birefringence and MSOME to distinguish different categories of sperm: nonbirefringent (category A), birefringent (category B), birefringent with nuclear vacuoles (category C), and birefringent with no nuclear vacuoles (category D). From each semen sample, sperm of any category were selected and further analyzed by TUNEL test. A total of 660 well-characterized sperm were evaluated for DNA fragmentation. Category A showed a low percentage of sperm with normal MSOME results (19.4%) and high prevalence of DNA fragmentation (70.3%). Category B had 81.8% normal MSOME results, and in this group 31.8% had fragmentated DNA. Category C showed 31.8% and 92.6% DNA fragmentation in sperm with small and large nuclear vacuoles, respectively. Birefringent sperm with normal MSOME results and no vacuoles showed the lowest percentage of fragmented DNA (2.8%). Sperm selection by birefringence or MSOME alone had one-third probability to select sperm with fragmented DNA. The lowest percentage of DNA fragmentation was found in birefringent sperm with no nuclear vacuoles and normal MSOME results. We suggest combining both methods using a single microscope and selecting sperm without nuclear vacuoles to get sperm with a higher chance of having intact DNA.